2003
DOI: 10.1046/j.1365-2672.2003.01904.x
|View full text |Cite
|
Sign up to set email alerts
|

The microbiological quality of washing-up water and the environment in domestic and commercial kitchens

Abstract: Aims: To determine the microbiological quality of washing-up water and the environment in domestic and commercial kitchens. Methods and Results: Chicken meals were prepared by people without food safety training in their own kitchen (n ¼ 52) or by trained staff in a commercial kitchen (n ¼ 10). Study participants then washed-up, cleaned the kitchen and completed a food hygiene questionnaire. The temperature and microbiological quality of the washingup water, and the presence of pathogens in dishcloths, tea tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 13 publications
1
32
0
3
Order By: Relevance
“…Washing with detergent at elevated temperatures is usually the most common practice to eliminate bacteria on the food contact surfaces. Unfortunately, it was reported that S. typhimurium, S. enteritidis, C. jejuni and E. coli can survive after regular washing processes [50]. Moreover, bacteria can survive on the surfaces of cutting boards and stainless steel after washing with detergent.…”
Section: According To the Food And Drug Administration Of Unitedmentioning
confidence: 99%
“…Washing with detergent at elevated temperatures is usually the most common practice to eliminate bacteria on the food contact surfaces. Unfortunately, it was reported that S. typhimurium, S. enteritidis, C. jejuni and E. coli can survive after regular washing processes [50]. Moreover, bacteria can survive on the surfaces of cutting boards and stainless steel after washing with detergent.…”
Section: According To the Food And Drug Administration Of Unitedmentioning
confidence: 99%
“…But in real-life situations, tableware cleaning at the minimum required temperature may not always occur. Mattick et al (2003) confirmed this when they focused on the microbiological quality of cleaning water used by volunteers during a tableware washing exercise. They found cleaning water >40 C had significantly lower aerobic plate counts than cleaning water <40 C. According to Pfund (2004), temperatures !40 C may be uncomfortable for dishwashing employees and thus this minimum temperature is not consistently achieved.…”
Section: Comparative Efficiencies Of Manual With Mechanical Warewashimentioning
confidence: 74%
“…Mechanical washing, conversely, usually uses higher washing temperature (55e65 C) and is not subject to the discomfort experienced by human workers (Wernersson, Jeppsson, & Hakanson, 2006). Other factors that vary the efficacy of manual washing are the number and sizes of the tableware items to be washed, the initial microbial load, the type of food soil contaminating the tableware items and the time designated to clean them (Lee et al, 2007;Mattick et al, 2003;Montville, Chen, & Schaffner, 2002).…”
Section: Comparative Efficiencies Of Manual With Mechanical Warewashimentioning
confidence: 99%
“…Ingredientes usados crus, que podem abrigar microrganismos potencialmente patogênicos, são freqüentemente manipulados em cozinhas domésticas, tornando as superfícies de contato uma importante fonte de infecção (MATTICK et al, 2003). Manipulação e preparação inadequadas, tempo de armazenamento e cozimento impróprios, assim como capacidade de refrigeração das geladeiras domésticas, podem atuar como fatores de proliferação desses microrganismos.…”
Section: )unclassified
“…sobrevivem nas mãos, esponjas e panos de prato. Panos de prato podem se tornar altamente contaminados com diversas populações microbianas em um curto período de uso (MATTICK et al, 2003). S. aureus, por exemplo, continua viável em superfícies secas, como aço inox, por horas e até dias (KUSUMANINGRUM et al, 2003).…”
Section: )unclassified